The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.33448/rsd-v11i1.24638
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of abdominal circumference for diagnosing overweight in six-to-seven-years-old children

Abstract: Objective: To estimate the accuracy of abdominal circumference measurement as a method of diagnosing overweight in six-to-seven-years-old children. Methods: A cross-sectional study involving 1026 six-to-seven-years-old schoolchildren in southern Brazil was carried out. Children’s weight and height were collected at schools. Body mass index were calculated and categorized in z-score in eutrophy, overweight and obesity. Abdominal circumference was measured in centimeters with a tape with children in standing pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…On the contrary, other diagnostic methods have been proposed to help measure childhood obesity, such as waist circumference 4 and neck circumference 5 . The latter showed an important correlation with metabolic syndrome parameters and has a very low cost 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, other diagnostic methods have been proposed to help measure childhood obesity, such as waist circumference 4 and neck circumference 5 . The latter showed an important correlation with metabolic syndrome parameters and has a very low cost 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies 4 , 5 , 7 have shown a relationship between childhood overweight and obesity and neck circumference, being potentially as effective as waist circumference and BMI in measuring overweight and obesity. In 6-year-old children, neck circumference presented an accuracy of 77.2% as a diagnostic method for overweight.…”
Section: Introductionmentioning
confidence: 99%